2012
DOI: 10.1021/jp3027463
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Impedance Analysis of Adsorption and Enzyme Kinetics of Calf Intestine Alkaline Phosphatase on SAM-Modified Gold Electrode

Abstract: In this work, we have explored the potential of electrochemical impedance technique to follow the kinetics of nonspecific adsorption of enzymes on to a self-assembled monolayer (SAM) of 3-mercapto benzoic acid (3-MBZ) formed on gold electrodes. We have also studied kinetics of enzyme− substrate reactions on the immobilized surface using this technique. During the adsorption process, the surface coverage is measured using the imaginary component of the impedance at a given frequency, which was found to follow L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…139 The adsorption behavior and mechanism of enzymes on highly oriented pyrolytic graphite, CNTs, nanoporous materials, self-assembled monolayer (SAM) on gold, and dipalmitoylphosphatic acid monolayer have been extensively investigated recently. [138][139][140][141][142][143][144][145][146][147] Covalent attachment is considered as one of the most effective methods for the stable immobilization of enzymes and is widely employed to fabricate biosensors. [148][149][150] For instance, Xu et al reported the covalent immobilization of GOx on well-defined poly(glycidyl methacrylate)-Si (111) hybrids from surface-initiated atom-transfer radical polymerization and the immobilized GOx exhibited a corresponding relative activity of about 60% and an improved stability during storage over that of the free enzyme.…”
Section: The Immobilization Of Enzymes On Sensing Electrodesmentioning
confidence: 99%
“…139 The adsorption behavior and mechanism of enzymes on highly oriented pyrolytic graphite, CNTs, nanoporous materials, self-assembled monolayer (SAM) on gold, and dipalmitoylphosphatic acid monolayer have been extensively investigated recently. [138][139][140][141][142][143][144][145][146][147] Covalent attachment is considered as one of the most effective methods for the stable immobilization of enzymes and is widely employed to fabricate biosensors. [148][149][150] For instance, Xu et al reported the covalent immobilization of GOx on well-defined poly(glycidyl methacrylate)-Si (111) hybrids from surface-initiated atom-transfer radical polymerization and the immobilized GOx exhibited a corresponding relative activity of about 60% and an improved stability during storage over that of the free enzyme.…”
Section: The Immobilization Of Enzymes On Sensing Electrodesmentioning
confidence: 99%
“…Another one was the adsorption approach, which is similar to immobilization. Shrikrishnan et al (2012) detected ALP on a self-assembled monolayer modified gold electrode [126]. Their results show a decrease in impedance resolution when the protein of ALP adsorbed on to the monolayer due to the increment of ionic charges resulting in their reactions.…”
Section: Other Detection Techniquesmentioning
confidence: 99%
“…Voltammetric detection of the produced p-aminophenol was performed with a platinum wire as the auxiliary electrode and a Ag=AgCl electrode as the the reference electrode. Other buffer systems such as phosphate (Han et al 2013;Shrikrishnan, Sankaran, and Lakshminarayanan 2012), diethanolamine (Kanso et al 2013) and 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (Tekaya et al 2013) have also been employed for the alkaline phosphatasemediated dephosphorylation reaction. In this work, Tris buffer was used for the enzyme catalytic reaction and the electrochemical experiment, as reported by (Akanda et al 2013;Kim et al 2003).…”
Section: Determination Of Mucinmentioning
confidence: 99%